Upaya Meningkatkan Pengetahuan Remaja dalam Mengatasi Adiksi Gadget - Renylda, Reta; Yan, Loriza Sativa (LPPM Universitas Bumigora, 2023)
Abstract: Gadget addiction became a serious problem for teenagesrs aged groups. Excessive gadgets also caused health problems, behavior changes, and attitudes in teenager aged. Knowledge aspect was important to help in shaping positive behavior. This community service activity is carried out with health education and visualization methods. These activities aimed to increase teenager knowledge in overcoming gadget addiction. Data collected by smartphone addiction with the number of participants of 50 students of SMP N 2 Kota Jambi. After the pretest and posttest processes have shown the results of increasing adolescent knowledge and understanding in overcoming the impact of gadget addiction. The results indicated that increasing knowledge is needed for efforts to improve teenager with an interactive media approach for this school as ongoing basis.